ANALISIS DAMPAK PERISTIWA DIVESTITURE ANOUNCEMENT DAN FINANCIAL STATEMENT RESTATEMENT TERHADAP MARKET REACTION PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2015 - Sahputra, Krishna; Diantimala, Yossi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this research is to analyze the impact of divestiture announcement and financial statement restatement events upon market reactin abnormal return in company which registered at Indonesia Stock Exchange from 2010 until 2015 using cumulative abnormal return during seven days before and after even. The type of data used in this research is secondary data which obtained from financial statements publishing by capital market reference center that existed in Indonesia Stock Exchange. The sample used in this research is study case with the total of the population is 539 companies. Method used in this research is purposive sampling which yielded 20 companies sample for divestiture announcement event and 15 companies sample for financial statement restatement event. Meanwhile, the examination of hypothesis used is event study method. The result of this research illustrate that divestiture announcement and financial statement restatement events did not give an impact upon market reaction. However, in case of considering each variable, there is a difference between before and after the occurrence of divestiture announcement and financial statement restatement events.